UNRAVELING THE MEDICAL QUALITY OF CARE FOR POSTOPERATIVE PRIMARY RETINAL DETACHMENT - Wang, Mei-Ling; Liu, Chih-Hao (American Journal of Public Health and Epidemiology (AJPHE), 2023)
The retina, a crucial component of the human visual system, is responsible for capturing and processing external visual information. It functions much like a camera, and its health is closely intertwined with the choroidal blood vessels that provide essential nutrients. When the nerve layer and pigment layer connected to the retina become detached, a condition known as retinal detachment, vision is profoundly affected due to the loss of nutrition. Myopia, a common vision disorder, has been linked to an increased risk of retinal detachment, particularly in cases of high myopia. Myopia rates have been soaring, especially among young people, and it is often associated with the educational environment. Studies have identified myopia-related pathological changes as a significant contributor to low vision and blindness. This research also underlines the importance of identifying risk factors for retinal detachment, beyond myopia. Ophthalmic surgery, notably cataract procedures, and eye/head trauma have been recognized as potential risk factors. Furthermore, the study sheds light on the potential influence of occupational factors, with manual and high-risk occupations appearing to correlate with a higher incidence of retinal detachment. Educational attainment and socio-economic status have emerged as additional risk factors, possibly due to the relationship between higher education levels and myopia. The progression of retinal detachment is marked by early symptoms such as vitreous floaters and flashes. Over time, as the retinal detachment hole enlarges and approaches the macular center, peripheral vision defects become apparent and eventually affect central vision. This gradual loss of vision can be debilitating and emphasizes the critical importance of early detection and intervention. Given the substantial impact of retinal diseases on public health and epidemiology, it is imperative to address this issue. In Taiwan, retinal detachment is a major cause of blindness, with an estimated one to two thousand cases occurring each year. Left untreated, it leads to severe vision impairment and, ultimately, blindness. Awareness, prevention, and timely treatment are essential to mitigate the devastating consequences of retinal detachment